0.4(2x+3)=-0.2+(-3)-5

Simple and best practice solution for 0.4(2x+3)=-0.2+(-3)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.4(2x+3)=-0.2+(-3)-5 equation:



0.4(2x+3)=-0.2+(-3)-5
We move all terms to the left:
0.4(2x+3)-(-0.2+(-3)-5)=0
We add all the numbers together, and all the variables
0.4(2x+3)+8.2=0
We multiply parentheses
0.8x+1.2+8.2=0
We add all the numbers together, and all the variables
0.8x+9.4=0
We move all terms containing x to the left, all other terms to the right
0.8x=-9.4
x=-9.4/0.8
x=-11+0.6/0.8

See similar equations:

| Y=a(a-2)(a-a) | | -12=z÷3. | | ((2x-8)/3+5=6-((3x-5)/4 | | k+1/2=-8 | | 10x+60=90 | | N^2+5n-9=0 | | 24x=4(6x) | | 56=v | | 140=6x+20 | | 2x+64=122 | | 5y+2y=24 | | 10/n=7/13 | | -(e+5)+10=-(6+e) | | 7.3x-12.7=38.4 | | -(e-5)=10=-(6+e) | | 2x-8=4x-3 | | 4–3y=31 | | x+2x+6x=72 | | 95+14x=-59 | | X=12x-8 | | x2+(x-4)2=328 | | (X)(X)+(x-4)(x-4)=328 | | -3x²-2x+9=x²+2x+10 | | 27^-3x=243^-x | | -k+k=-10 | | -21=-y/9 | | 27-3x=243^-x | | 4x+1=141 | | E=3c*3c | | X-3-2x-7=0 | | 2+3x=44 | | (x-4)=(x²-8x+16) |

Equations solver categories